Ekman and eddy exchange of freshwater and oxygen across the Labrador Shelf break - Howatt, Tara; Palter, Jaime B.; Matthews, John Brian Robin; deYoung, Brad; Bachmayer, Ralf; Claus, Brian (Journal of Physical Oceanography, 2018)
Transport of freshwater from the Labrador Shelf into the interior Labrador Sea has the potential to impact deep convection via its influence on the salinity of surface waters. To examine this transport, the authors deployed two underwater gliders on a mission to traverse the continental shelf break multiple times between 5 July and 22 August 2014, the period when Arctic meltwater has historically peaked in transport down the Labrador Shelf. The field campaign yielded a unique dataset of temperature, salinity, and oxygen across the shelf break to a depth of 1000 m at unprecedented spatial resolution. Two mechanisms of cross-shelf transport were examined: Ekman transport and transport due to mesoscale eddies. Ekman transport is quantified using satellite wind stress and near-surface hydrographic properties, and eddy-induced transport is scaled using a parameterized eddy diffusivity and thickness gradients of layers of uniform potential density, as well as the tracer gradients along those isopycnals. Both the Ekman and eddy terms transport high-oxygen and low-salinity water from the shelf to the Labrador Sea during the field campaign. The influence of the eddy-driven oxygen flux from the shelf to the Labrador Sea on oxygen budgets depends strongly on the size of the region over which this eddy flux converges. The deduced offshore transport of freshwater (4 ± 6 mSv; 1 mSv = 103 m3 s-1) from both Ekman and eddy mechanisms, which is likely at a seasonal maximum during this summertime survey, represents about 3% of the annual-mean freshwater flowing through Hudson and Davis Straits but may be an important component of the total freshwater budget of the interior Labrador Sea.